Challenges for future library / Ain Farzanah Mohd Husaini, Siti Nur Aishah Mansor and Susriyanna Supardi - Mohd Husaini, Ain Farzanah; Mansor, Siti Nur Aishah; Supardi, Susriyanna (Faculty of Information Management, 2014)
According to Harold's Librarian Glossary, library defined as a collection of book and other literacy materials kept for reading, research, references, study and consultation. The word library was derived from Latin's word 'liber' or 'libri' which mean book or writing. Library is a center of information that hold variety of knowledge.